A metabolomic analysis of thiol response for standard and modified N‐acetyl cysteine treatment regimens in patients with acetaminophen overdose - Dear, James W; Ng, Mei Li; Bateman, D. Nicholas; Leroy Sivappiragasam, Pakkiri; Choi, Hyungwon; Khoo, Benjamin Bing Jie; Ibrahim, Baharudin; Drum, Chester Lee (Clinical and translational science, 2021)
N‐acetylcysteine (NAC) is an antidote to prevent acetaminophen (paracetamol‐APAP)‐induced acute liver injury (ALI). The 3‐bag licensed 20.25 h standard regimen, and a 12 h modified regimen, are used to treat APAP overdose. This study evaluated the redox thiol response and APAP metabolites, in patients with a single APAP overdose treated with either the 20.25 h standard or 12 h modified regimen. We used liquid chromatography tandem mass spectrometry to quantify clinically important oxidative stress biomarkers and APAP metabolites in plasma samples from 45 patients who participated in a randomized controlled trial (SNAP trial). We investigated the time course response of plasma metabolites at predose, 12 h, and 20.25 h post‐start of NAC infusion. The results showed that the 12 h modified regimen resulted in a significant elevation of plasma NAC and cysteine concentrations at 12 h post‐infusion. We found no significant alteration in the metabolism of APAP, mitochondrial, amino acids, and other thiol biomarkers with the two regimens. We examined APAP and purine metabolism in overdose patients who developed ALI. We showed the major APAP‐metabolites and xanthine were significantly higher in patients with ALI. These biomarkers correlated well with alanine aminotransferase activity at admission. Receiver operating characteristic analysis showed that at admission, plasma APAP‐metabolites and xanthine concentrations were predictive for ALI. In conclusion, a significantly higher redox thiol response with the modified NAC regimen at 12 h postdose suggests this regimen may produce greater antioxidant efficacy. At baseline, plasma APAP and purine metabolites may be useful biomarkers for early prediction of APAP‐induced ALI.